Recombinant multimeric dog allergen prevents airway hyperresponsiveness in a model of asthma marked by vigorous TH2 and TH17 cell responses. Issue 10 (20th June 2022) - Stark, Julian M.; Liu, Jielu; Tibbitt, Christopher A.; Christian, Murray; Ma, Junjie; Wintersand, Anna; Dunst, Josefine; Kreslavsky, Taras; Murrell, Ben; Adner, Mikael; Grönlund, Hans; Gafvelin, Guro; et al.
Abstract: Background: Allergy to dogs affects around 10% of the population in developed countries. Immune therapy of allergic patients with dog allergen extracts has shown limited therapeutic benefit. Methods: We established a mouse model of dog allergy by repeatedly administering dog dander and epithelium extracts via the intranasal route. We also assessed the efficacy of a recombinant multimeric protein containing Can f 1, f 2, f 4 and f 6 in preventing inflammatory responses to dog extracts. Results: Repeated inhalation of dog extracts induced infiltration of the airways by TH 2 cells, eosinophils and goblet cells, reminiscent of the house dust mite (HDM) model of asthma. Dog extracts also induced robust airway hyperresponsiveness and promoted TH 17 cell responses, which was associated with a high neutrophilic infiltration of the airways. scRNA‐Seq analysis of T helper cells in the airways pinpointed a unique gene signature for TH 17 cells. Analysis of T‐cell receptors depicted a high frequency of clones that were shared between TH 17, TH 2 and suppressive Treg cells, indicative of a common differentiation trajectory for these subsets. Importantly, sublingual administration of multimeric Can f 1‐2‐4‐6 protein prior to sensitization reduced airway hyperresponsiveness and type 2‐mediated inflammation in this model. Conclusion: Dog allergen extracts induce robust TH 2 and TH 17 cell‐mediated responses in mice. Recombinant Can f 1‐2‐4‐6 can induce tolerance to complex dog allergen extracts. Abstract : Intranasal administration of dog allergen extracts induces airway hyperresponsiveness and robust TH 17 cell‐driven neutrophilia. Single cell RNA‐Sequencing pinpoints distinct gene expression signatures between canonical TH cell subsets and shows considerable clonal overlap between TH 2, TH 17, Treg and TFH cells. A recombinant multimer of lipocalin allergens (Can f 1‐2‐4‐6) reduces TH 2 cell responses and airway hyperresponsiveness when administered prophylactically.Abbreviations: AHR, airway hyperresponsiveness; CCR6, C‐C motif chemokine receptor 6; CXCR5, C‐X‐C chemokine receptor 5; EOS, eosinophil; IL, interleukin; NEU, neutrophil; Tfh, follicular T helper cell; Treg, regulatory T helper cell